1970
DOI: 10.1192/bjp.117.540.571
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Contact and Depression: A Preliminary Report

Abstract: Riemer (1955) has argued that gaze is an ‘expression of affect’ between individuals. Kendon (1967) writes that the direction of gaze has a regulatory and expressive function, and ‘fluctuations in the amount of eye-contact during the course of one conversation showed that it was inversely related to the amount of emotionality displayed by the participants'. Also that it has a regulatory function which governs the pattern of social interaction. Argyle and Dean (1965) made similar observations in their concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…Personality disorder-specific traits can be accurately perceived in thin slices of nonverbal behavior, and even psychopathology can be accurately perceived in both videos of targets as well as facial photographs (e.g., Fowler et al, 2009;Friedman et al, 2007;Holtzman, 2011). Both depression and anxiety can be accurately perceived in thin slices (see Harrigan et al, 2004;Hinchliffe et al, 1970Hinchliffe et al, , 1971Waxer, 1974Waxer, , 1976Yang et al, 2013). State and trait anxiety, for instance, are both detectable in thin slices, but in different channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality disorder-specific traits can be accurately perceived in thin slices of nonverbal behavior, and even psychopathology can be accurately perceived in both videos of targets as well as facial photographs (e.g., Fowler et al, 2009;Friedman et al, 2007;Holtzman, 2011). Both depression and anxiety can be accurately perceived in thin slices (see Harrigan et al, 2004;Hinchliffe et al, 1970Hinchliffe et al, , 1971Waxer, 1974Waxer, , 1976Yang et al, 2013). State and trait anxiety, for instance, are both detectable in thin slices, but in different channels.…”
Section: Resultsmentioning
confidence: 99%
“…Depressed patients displayed more contraction of lower corners of their mouth (associated with negative emotion), looked downward more, and moved their hands less. Additionally, continuous judgments of the severity of depression predicted scores on the Minnesota Multiphasic Personality Inventory Depression scale (see also Hinchliffe, Lancashire, & Roberts, 1970). Another study comparing participants who had recovered from depression to those who were still depressed found that those who were still depressed maintained less mutual eye gaze (Hinchliffe, Lancashire, & Roberts, 1971).…”
Section: Depressionmentioning
confidence: 99%
“…Results of eye-tracking studies reveal that, compared to non-depressed controls, individuals with depression spend more time viewing negative images (e.g., sad faces) and less time with positive or neutral images (Kellough et al, 2008;Sanchez et al, 2013;Isaac, et al, 2014). Furthermore, research on clinical interviews has shown that patients with depression display less eye contact with mental health professionals than the patients with other psychiatric conditions such as schizophrenia (Jones and Pansa, 1979) and non-depressed controls (Hinchliffe et al, 1970;Sobin and Sackeim, 1997;Fiquer, et al, 2018). Interestingly, the avoidance of eye contact has been observed to emerge regardless of the severity of depression and to persist relatively long after treatment (Fiquer et al, 2018).…”
Section: Depression and Social Interactionmentioning
confidence: 99%
“…Reproduktion", welche nach Arieti (2) die Ausdrucksweise dieses Charaktertyps bestimmt, die Dynamik und den kommunikativen Austausch mit dem endogen Depressiven merklich hemmen, so bricht in der Krankheitsphase der Kontakt mit ihnen noch zusätzlich ab. Depressive haben im Vergleich zu psychisch gesunden Kontrollpersonen eine signifikante Reduktion des Redeflusses (25,53) und des Blickkontaktes (24,47). Nicht nur die allgemeine Hemmung des Antriebs und des Denkens dürfte ihre Gesprächsfahigkeit zusätzlich behindern, sondern auch ihre Unfähigkeit, sich selbst zu spüren und sich in eine Beziehung einzubringen (49).…”
Section: Dürfte Bereits Die "Fotografische Art Derunclassified